2020
DOI: 10.21203/rs.3.rs-16751/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anti-proliferative activities of Byrsocarpus coccineus Schum. and Thonn. (Connaraceae) using Ovarian Cancer Cell Lines

Abstract: Abstract Background: Ovarian cancer (OvCa) is one of the most lethal tumors of gynecologic malignancies, due to lack of early detection, and a high rate of metastasis. The standard treatment for OvCa is surgery and cytotoxic chemotherapy. However, to overcome the high cost and side effects of these treatments, medicinal plants are widely used in developing countries to treat OvCa. Byrsocarpus coccineus plant preparation has been administered to patients traditionally in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…& Thonn, which belongs to the family of Connaraceae, is widely used traditionally to treat inflammation related deseases. Many studies have shown that leaf extract of B. coccineus has hepatoprotective [15], antioxidant [15,16,17] and anti-proliferative effects [18]. In our previous study, ethanolic extract root bark of Rourea coccinea (EERc) was found to possess anti-inflammatory property [19] and antioxidant activity [20] but the underlying mechanism of these properties is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…& Thonn, which belongs to the family of Connaraceae, is widely used traditionally to treat inflammation related deseases. Many studies have shown that leaf extract of B. coccineus has hepatoprotective [15], antioxidant [15,16,17] and anti-proliferative effects [18]. In our previous study, ethanolic extract root bark of Rourea coccinea (EERc) was found to possess anti-inflammatory property [19] and antioxidant activity [20] but the underlying mechanism of these properties is unknown.…”
Section: Introductionmentioning
confidence: 99%